Անկախութեան օրակարգի ձեւաւորումը Անկախութեան հրապարակում եւ Գերագոյն խորհրդում - Զաքարեան, Լիլիթ (տպ. Atlas)
Armenia had become a part of the Soviet Union, not of its own free will, but rather in order to resolve the problem of its existence, and for the majority of the Soviet Armenians the strong multinational state of the Soviet Union seemed to be the only guarantee of Armenia’s security. During the Soviet years the Armenians lost some territory but accomplished huge socioeconomic and cultural achievements in the absence of freedom of thought and conscience. Things changed thanks to the policy of Prerestroika, which revived hopes of restoring historic justice. The Artsakh movement was one of Persetroika’s results. But the pogroms of Armenians in the Azerbaijai SSR and the intention of covering up those crimes, alongside anti-Armenian attacks in the Soviet mass media, gradually disappointed the Armenians. This put a question mark on the security concerns of the Armenians in the USSR. Next to the national liberation agenda there arose the issue of independence, which underwent three stages of development. The first stage, which was perhaps the most difficult and the longest, was the shaping of the concept of independence in the minds of the Armenian polity and its promotion as an agenda point. It resulted in the entrance of the opposition forces into the Soviet Armenian parliament. During the second stage a legal framework corresponding to the agenda of independence was shaped and the Independence Declaration was accepted. The third stage was the deepening of the process of independence, which ended with the referendum for independence. It is not easy to maintain a free and independent nation state. Today the Republic of Armenia is facing serious worldwide political challenges. Nevertheless, an independence generation has been formed that sees its future only in an independent state.
Keywords: Պատմութիւն; Հասարակակարգ